CREATION OF AUTOMOTIVE MARKET PREDICTION SYSTEM - KRYVENCHUK, YURII; VOVCHAK, LIUBOMYR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Automotive market prediction systems are becoming increasingly important in today’s realities. They are used to predict the vector of changes in the world car market for example, the increase in the share of electric cars or the growing popularity of station wagons. These systems can help manufacturers better understand the needs of the buyer and make timely changes in their strategy as needed. Automotive market forecasting systems can also help to match specific changes to the markets of different countries according to their needs. Providing a more objective approach to determining the company’s business plan, which will be based on the data that these systems will provide. And of course, salary forecasting systems can be useful for companies to make a business plan and calculate their finances, having a better understanding of further market changes, the company can make an appropriate budget, taking into account the costs of developing those changes that will be popular in the future. The practical value of this work is a system of forecasting automotive market trends, which can provide valuable information and help make more informed decisions that can bring the most benefit to the company. In addition, such a system will be very useful for investors. They will be able to know in advance the trends of the world market and invest in companies that are developing in a priority direction, which will greatly reduce investment risks. And, of course, such a program will greatly facilitate the life of the buyers themselves. Now the market will be regulated much faster and as soon as there is any need for changes - companies will be ready because they have been warned about this need for changes by our forecasting system. In this way, customers will be able to receive the most suitable product on time and without unnecessary costs for emergency development.